Effectiveness of the Schroth Method in Improving Cobb Angle, Trunk Rotation, and Quality of Life in Adolescents With Idiopathic Scoliosis: A Systematic Review - Arash Khaledi; Hooman Minoonejad; Hassan Daneshmandi; Mahdieh Akoochakian; Mehdi Gheitasi (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Idiopathic scoliosis is a complex three-dimensional deformity affecting the spine and is more common in adolescents (10-18 years). Failure to pay attention to it can increase its severity and complications. Various exercise methods have been designed for preventing, managing, or correcting adolescent idiopathic scoliosis (AIS). Among them, the Schroth method has attracted the attention of therapists due to its promising results. However, there is still conflicting evidence of its effectiveness. Therefore, this review study aims to investigate the effectiveness of the Schroth method in improving the Cobb angle, trunk rotation angle, and quality of life (QoL) in adolescents with idiopathic scoliosis. Methods This is a systematic review study. A search was conducted in Cochrane, PubMed, Medline, Scopus and Google Scholar databases for finding studies that used Schroth method as an intervention and published from 2005 to December 2021 using the keywords related to AIS. The PEDro scale was used to evaluate the quality of papers. Results Initial search yielded 96 records of which 10 papers with PEDro scale score of 5.8 were selected for the review. Among them, the variables of Cobb angle, QoL, ATR were evaluated in nine, six and four papers, respectively. The outcomes obtained from the papers showed the significant effect of Schroth method on reducing the Cobb angle (>5°, using radiography), trunk rotation (>3°, using scoliometer) and improving the QoL (Using the scoliosis research society questionnaire). In only one paper, despite a significant improvement in QoL, no significant reduction in Cobb angle (<5°) was observed. Conclusion There is moderate evidence of the positive effects of the Schroth method on improving Cobb angle, trunk rotation angle and QoL in adolescents with idiopathic scoliosis. This method can used for preventing from the worsening of AIS. It can be used along with other methods such as core stability exercises and Pilates. Since the reviewed studies had moderate quality, high-quality studies are needed in this field.